Black carbon indirect radiative effects in a climate model. Issue 1 (1st January 2017) - Cherian, Ribu; Quaas, Johannes; Salzmann, Marc; Tomassini, Lorenzo
Abstract: The aerosol–cloud interactions due to black carbon (BC) aerosols, as well as the implied climate responses, are examined using an aerosol module in the coupled atmosphere–ocean general circulation model MPI-ESM. BC is simulated to enhance cloud droplet number concentration (CDNC) by 10–15% in the BC emission source regions, especially in the Tropics and mid-latitudes. Higher CDNC and reduced auto-conversion from cloud water to rain water explains the increased cloud water path over the tropical regions (30 S–30 N) in the model. In the global mean, the cloud water– as well as precipitation changes are negligibly small. The global-mean effective radiative forcing due to aerosol–cloud interactions for BC is estimated at, which is attributable to the increase in CDNC burden and (regionally) cloud water in the model. Global mean temperature and rainfall response were found to be and, respectively, with significantly larger regional changes mainly in the downwind regions from BC sources.